Gestão de águas pluviais urbanas através da abordagem Water Sensitive Urban Design : desafios e potencialidades para o município de São Carlos - SP - Faustino, Alexandre da Silva (Universidade Federal de São Carlos, 2017)
Conflicts over water are inherent in the development of cities and stand out in the setting of environmental and urban crisis scenarios. New models of urban management and planning congruent to the hydrological cycle suggest more harmonious relations between the urbanization process and ecosystem interventions, to efficiently take advantage of the natural characteristics of the environment. Water Sensitive Urban Design (WSUD) has emerged from this premise to meet the demands of the Australian context. Currently the practices that follow this approach have multiplied, forming a set of experiences that can guide the dissemination of WSUD to other realities, such as the Brazilian cities scenario. This research proposed the study of this approach in its origins, as well as the understanding of the water cycle vision adopted in urban planning of the São Carlos city, aiming to demonstrate the potentialities and limitations of WSUD application in the urban stormwater management and planning of this municipality. The research was structured in four phases: exploratory, descriptive, analytical and conclusive. Each of these phases allowed to carry out a theoretical background that bases the discussions of the dissertation, to obtain an approximation of the characteristics of the objects studied and to develop analyses about the used procedures and founded results. It was possible to systematize a framework of the approach from technical manuals, to compile historical and contemporary processes that condition the conflicts between urbanization and the conservation of water ecosystems in the city of São Carlos, and to build a matrix of potentialities and weaknesses about the development of WSUD in this context, intending for the advancement of the issue in prospects of reduced impact and greater environmental and urban health for the municipality. It was verified that the urbanization process of São Carlos had been oriented by the conventional paradigm of stormwater management setting up a scenario of Drained City, but since 2001 institutional and legal transitions allowed the emergence of alternative practices, which established potentialities to foster the Water Sensitive City. Based on the presented results, possible strategies were adopted for the management of rainwater management that allow the implementation of alternative practices.
Urban stormwater management by the Water Sensitive Urban Design approach: challenges and opportunities for the municipality of São Carlos - SP
Keywords: Gestão urbana; Manejo de águas pluviais; Sustentabilidade ambiental urbana; Urban management; Stormwater management; Environmental urban sustainability; CIENCIAS SOCIAIS APLICADAS::PLANEJAMENTO URBANO E REGIONAL::METODOS E TECNICAS DO PLANEJAMENTO URBANO E REGIONAL